Biotechnology Fundamentals - Firdos Alam Khan (CRC Press, 2016)
A single source reference covering every aspect of biotechnology, Biotechnology Fundamentals, Second Edition breaks down the basic fundamentals of this discipline, and highlights both conventional and modern approaches unique to the industry. In addition to recent advances and updates relevant to the first edition, the revised work also covers ethics in biotechnology and discusses career possibilities in this growing field. The book begins with a basic introduction of biotechnology, moves on to more complex topics, and provides relevant examples along the way. Each chapter begins with a brief summary, is illustrated by simple line diagrams, pictures, and tables, and ends with a question session, an assignment, and field trip information. The author also discusses the connection between plant breeding, cheese making, in vitro fertilization, alcohol fermentation, and biotechnology.